Additive‐Free Self‐Presodiation Strategy for High‐Performance Na‐Ion Batteries. (17th April 2021) - Ding, Feixiang; Meng, Qingshi; Yu, Pengfei; Wang, Haibo; Niu, Yaoshen; Li, Yuqi; Yang, Yang; Rong, Xiaohui; Liu, Xiaosong; Lu, Yaxiang; Chen, Liquan; Hu, Yong‐Sheng
Abstract: The irreversible consumption of sodium at the anode side during the first cycle prominently reduces the energy density of Na‐ion batteries. Different sacrificial cathode additives have been recently reported to address this problem; however, critical issues such as by‐products (e.g., CO2 ) release during cycling and incompatibility with current battery fabrication procedures potentially deteriorate the full‐cell performance and prevent the practical application. Herein, an additive‐free self‐presodiation strategy is proposed to create lattice‐coherent but component‐dependent O3‐Na x TMMnO2 (TM =  transition metal ion(s)) cathodes by a quenching treatment rather than the general natural cooling. The quenching material preserves higher Mn 3+ and Na + content, which is able to release Na + via Mn 3+ oxidation to compensate for sodium consumption during the initial charge while adopting other TM to provide the capacity in the following cycles. Full cells fabricated with hard carbon anode and this material as both cathode and sodium supplement reagent have a nearly 9.4% cathode mass reduction, around 9.9% energy density improvement (from 233 to 256 Wh kg −1 ), and 8% capacity retention enhancement (from 76% to 84%) after 300 cycles. This study presents the route to rational design cathode materials with sodium reservoir property to simplify the presodiation process as well as improve the full‐cell performance. Abstract : An additive‐free self‐presodiation strategy is proposed for the rational design of Na‐ion battery (NIB) cathode materials to compensate for the irreversible consumption of sodium at the anode side during the first cycle of NIBs. The as‐prepared O3‐Na x TMO2 cathodes preserve higher Na + and Mn 3+ content by a quenching treatment, rendering it not only the cathode but also a sodium donor.